Two-Phase Study to Assess the Number of Cases Based on Claims Databases: Characteristics of the Validation Data Set - Couris, C. M.; Rabilloud, M.; Colin, C.; Ecochard, R. (Methods of Information in Medicine, 2002)
Objective: In a two-phase study design, the characteristics of an external data set were studied for precision and bias of the number of incident or prevalent cases of a disease obtained from claims databases.Methods: In the study population (first phase), incident or prevalent cases were counted whereas external data (second phase) provided sensitivity and specificity estimates to count cases in a claims database. Influence of potential differences in sensitivity and specificity between the two phases were evaluated. This was illustrated for 50-90% sensitivity and 99-99.99% specificity ranges.Results and Conclusions: The impact of differences in sensitivity and specificity depends on the odds of disease in the study population. We provide advice on the choice of adequate data sets to correct claims database estimates.
Keywords: Medical informatics applications; incidence; sensitivity and specificity; statistics; epidemiology